A new species of Trichotosia from Sabah, Malaysian Borneo - Norhslinda Maleka; Lamb, Anthony; Monica Suleiman (Natural History Publications Borneo, 2013)
Trichotosia is listed by Wood et al. (1993) as one of several poorly known orchid genera from Borneo. The variously hairy vegetative parts and flowers are unique among the orchids of Borneo. However, lack of comprehensive representative collections in herbaria, limited references in the literature, and generally small flowers make identification difficult. Herbarium collections also often lack flowers, identification being possible to genus level only.